STREET FOOD VENDORS’ HYGIENE AND SANITATION PRACTICE IN JAKARTA STREET FOOD COURTS (PUJASERA) - Anton Harianto; Edvi Gracia Ardani (Universitas Multimedia Nusantara, 2021)
Abstract- The existence of food street vendors in Jakarta Indonesia has been regulated by a Governor regulation for its improved management and arrangement in 2015. The food street vendors were unregulated and uncontrollable that disturb other street users, become organized with infrastructure support and empowerment plan from the government. The support structure from the local government is to construct food street courts to give basic facilities required for such business. The evolution from unregulated street vendors to a more organized locus for street vendors was supposed to be supported by empowerment. The study aims to investigate how food street vendors feels in facing the changes of business situation in general. For this purpose, a qualitative method with descriptive approach using observations and in-depth interview with the food street vendors. The findings of the research show that the food street vendors feel more confident in selling their food product whereas they have not implemented hygiene and sanitation as it is supposed to be. Thus, it is recommended to enhance the empowerment plan by looking at closely on the communication media to develop the capacity of the food street vendors. Keywords: Food Hygiene; Micro Business; Street Food; Street Vendor Sanitation